2009
DOI: 10.1111/j.1475-682x.2008.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Why the Sociology of Morality Needs Bourdieu's Habitus*

Abstract: Though Pierre Bourdieu has been criticized for ignoring the moral dimensions of social judgments, I suggest that his habitus concept can provide a useful theoretical foundation for a sociological analysis of morality. If the habitus is revised in a way that recognizes the embodied nature of cognition, it can be treated as a foundation for moral judgments of the self and of others. A revised habitus concept can account for two processes by which moral judgments are shaped by social settings: (1) cultural influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 60 publications
2
70
0
1
Order By: Relevance
“…It is only in the past 15 years, however, that a growing call for a systematic sociology of morality has emerged (see, for example, Stivers, 1996;Thiele, 1996;Davydova & Sharrock, 2003;Pharo, 2005;Zdrenka, 2006;Abend, 2008;Ignatow, 2009;Swartz, 2009;Kang & Glassman, 2010). Amongst these, Abend (2008), argues for sociological inquiry into morality focused on 'empirical accounts of people's moral beliefs, and their causes and consequences' (p. 120); Pharo (2005), drawing on Pierre Bourdieu's (1997) social and cultural reproduction theory, argues that the concept of choice, prevalent in conventional moral discourses, be replaced by an analysis of 'social settings [that] do not depend on agents' decisions…[but on] situations like scarcity of goods, lack of political liberty, sexual oppression, restriction of social perspectives' (no page numbers on text); and Thiele (1996) advocates a sociology of morality that investigates the origins and 'disputes' concerning moral authority' (p. 7).…”
Section: The Sociology Of Moralitymentioning
confidence: 99%
“…It is only in the past 15 years, however, that a growing call for a systematic sociology of morality has emerged (see, for example, Stivers, 1996;Thiele, 1996;Davydova & Sharrock, 2003;Pharo, 2005;Zdrenka, 2006;Abend, 2008;Ignatow, 2009;Swartz, 2009;Kang & Glassman, 2010). Amongst these, Abend (2008), argues for sociological inquiry into morality focused on 'empirical accounts of people's moral beliefs, and their causes and consequences' (p. 120); Pharo (2005), drawing on Pierre Bourdieu's (1997) social and cultural reproduction theory, argues that the concept of choice, prevalent in conventional moral discourses, be replaced by an analysis of 'social settings [that] do not depend on agents' decisions…[but on] situations like scarcity of goods, lack of political liberty, sexual oppression, restriction of social perspectives' (no page numbers on text); and Thiele (1996) advocates a sociology of morality that investigates the origins and 'disputes' concerning moral authority' (p. 7).…”
Section: The Sociology Of Moralitymentioning
confidence: 99%
“…Like many of our colleagues (e.g., Lizardo 2004Lizardo , 2009Ignatow 2007Ignatow , 2009, this volume), we are quite optimistic about bringing together cognitive science and the Bourdieusian tradition and we hope our argument is interpreted with this in mind. Our concern is that the Bourdieusian distaste for "dualisms" risks rendering this cross-pollination less fruitful than it might otherwise be.…”
Section: The Old One-two: Preserving Analytical Dualism In Psychologimentioning
confidence: 83%
“…The second belief is that sociologists should pay more attention to research in the cognitive sciences (used here broadly to include psychology, neuroscience, and related disciplines) to outline a set of cognitively realistic principles that can inform the construction of a better theory of action (see e.g., DiMaggio 1997;Lizardo 2007;Vaisey 2009). The third belief is that the theoretical tradition of Pierre Bourdieu can serve as a bridge between sociology and the cognitive sciences that will facilitate better answers to questions about why people do the things they do (Lizardo 2004;Ignatow 2009;Vaisey 2009). …”
Section: The Old One-two: Preserving Analytical Dualism In Psychologimentioning
confidence: 99%
“…Despite the obvious implications of the habitus concept for understanding the macromicro dynamics of social morality, Bourdieu largely ignored the ethical dimensions of social judgments (Ignatow 2009;Lamont 1992;Sayer 2005). Ignatow (2009Ignatow ( , 2010 has suggested that a modified habitus concept, one that recognizes the embodied nature of cognition, provides a helpful framework for sociological analyses of morality.…”
Section: Power Asymmetries Habitus and The Constitution Of Moralitymentioning
confidence: 98%
“…Ignatow (2009Ignatow ( , 2010 has suggested that a modified habitus concept, one that recognizes the embodied nature of cognition, provides a helpful framework for sociological analyses of morality. According to Bourdieu (1984), the habitus comprises bodily phenomena (e.g., posture, manners, and accent) and cognitive schemas, both of which come into play when making moral judgments.…”
Section: Power Asymmetries Habitus and The Constitution Of Moralitymentioning
confidence: 99%